Lessons from the similarities and differences in fluid resuscitation between burns and sepsis: a bibliometric analysis - Dongxu Zhou; LuLu He; Wei Shi; Penglin Ma (Frontiers in Medicine)
BackgroundFluid is an essential component of initial resuscitation in sepsis or burns. Meanwhile, the optimal strategy of titrating fluids for both of the two conditions remains uncertain. In this bibliometric analysis, we compared the similarities and differences in fluid resuscitation between sepsis and burns in recent publications.MethodsLiteratures related to fluid resuscitation in either sepsis or burns were searched in the Web of Science database Core Collection from January 1, 1992, to December 31, 2022. CiteSpace and VOSviewer was used for bibliometric analysis.ResultsA total of 1,549 and 468 publications on fluid resuscitation in sepsis and burns were retrieved from 1992 to 2022. Based on the occurrences, 341 and 86 high-frequency keywords were screened out from sepsis and burns publications, respectively, which were similarly categorized into 5 clusters [i.e. “mechanisms of hypovolemia” (cluster 1), “titration of fluid” (cluster 2), “outcomes or complications” (cluster 3), “pathophysiological alternations” (cluster 4), and “fluid types and others” (cluster 5)]. The high-frequency keywords of the top 20 were more concentrated in cluster 3 and cluster 2, with “mortality” ranked the top in both sepsis and burns literature. Significantly, 3 keywords in cluster 2 ranked in the top 5, including “goal directed resuscitation” (the 3rd), fluid responsiveness (the 4th) and fluid balance (the 5th) in sepsis literature, while the keywords of “microvascular exchange” (cluster 1) and “abdominal compartment syndrome” (ACS, cluster 3) ranked at the second and the fifth place in burns publications. Keyword burst analysis demonstrated that the keyword with the highest burst strength (BS) was “formula” (BS = 5.88, 2008–2014), followed by management (BS = 4.79, 2012–2022), ACS (BS = 4.76, 2006–2010), and fluid creep (BS = 4.74, 2011–2016) in burn publications, but they were dobutamine (BS = 12.31, 1992–2008), cardiac output (BS = 9.79, 1993–2001), catecholamine (BS = 9.54, 1993–2006), and consumption (BS = 7.52, 1992–2006) in sepsis literature. Moreover, the most frequently cited article in either sepsis or burns was categorized into cluster 2, that investigated goal-directed fluid therapy for sepsis and formula improvement for burns resuscitation.ConclusionIt was demonstrated that the research priorities in titrating fluid were mainly concentrated on targeting hemodynamics in sepsis vs. improving formula (which briefly calculates the increased microvascular permeability) in burns, while concerning of “outcomes and complications” in fluid resuscitation similarly after 1992. However, hemodynamics and microvascular permeability have been simultaneously well considered in few previous studies regarding fluid resuscitation in either sepsis or burns.